Faktor – Faktor Yang Mempengaruhi Ketepatan Waktu Pelaporan Keuangan Pada Tahun 2015 – 2017: Keywords: Profitability; size; liquidity; age; & leverage - Ferry Abdillah Habibie; Ni Nyoman Alit Triani (Jurnal Akuntansi, 2022)
Fluctuations occur in a number of companies which not report their financial statements on time from 2015-2017. From these events it is necessary to make research that aims to determine the effect of profitability, company size, liquidity, age, and leverage on the timeliness of financial reporting (timeline) on all companies listed on the Indonesia Stock Exchange (IDX) in 2015 - 2017. Research using purposive sampling obtained 424 companies in accordance with the sampling method criteria. The analytical technique used logistic regression analysis by SPSS 23 which results that profitability & company size have positive effect on timelines. Whereas the variable liquidity, company age, and leverage have no effect on timelines.